2007
DOI: 10.1111/j.1432-0436.2006.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hoxa2 in cells entering chondrogenesis impairs overall cartilage development

Abstract: Vertebrate Hox genes act as developmental architects by patterning embryonic structures like axial skeletal elements, limbs, brainstem territories, or neural crest derivatives. While active during the patterning steps of development, these genes turn out to be down-regulated in specific differentiation programs like that leading to chondrogenesis. To investigate why chondrocyte differentiation is correlated to the silencing of a Hox gene, we generated transgenic mice allowing Cre-mediated conditional misexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…For instance, Hoxa2, which is overexpressed in BA1 cells of Ezh2 cko embryos, is a well-known inhibitor of intramembranous bone formation from BAs, and when overexpressed in the Hox-negative domain of avian embryos impairs formation of the facial skeleton (Couly et al, 1998;Creuzet et al, 2002;Kanzler et al, 1998). Massip and colleagues have shown that ectopic expression of Hoxa2 in chondrocytes results in impaired differentiation, as demonstrated by the lack of Col2a1, and prevents cartilage formation (Massip et al, 2007). In BA2, Hoxa2 is a promoter of the hyoid fate of mesenchymal CNCCs and restricts the chondrogenic domains that arise during endochondral ossification (Pasqualetti et al, 2000).…”
Section: Ezh2 Activity Silences Hox Gene Expression In Cnccsmentioning
confidence: 99%
“…For instance, Hoxa2, which is overexpressed in BA1 cells of Ezh2 cko embryos, is a well-known inhibitor of intramembranous bone formation from BAs, and when overexpressed in the Hox-negative domain of avian embryos impairs formation of the facial skeleton (Couly et al, 1998;Creuzet et al, 2002;Kanzler et al, 1998). Massip and colleagues have shown that ectopic expression of Hoxa2 in chondrocytes results in impaired differentiation, as demonstrated by the lack of Col2a1, and prevents cartilage formation (Massip et al, 2007). In BA2, Hoxa2 is a promoter of the hyoid fate of mesenchymal CNCCs and restricts the chondrogenic domains that arise during endochondral ossification (Pasqualetti et al, 2000).…”
Section: Ezh2 Activity Silences Hox Gene Expression In Cnccsmentioning
confidence: 99%
“…It is thought that HOX regulation of collagen subtypes imparts regional differences in the mechanical properties of tissues. Further, HOXA family genes have been implicated in the regulation of expression of key proteins involved in dynamic tissue and ECM remodeling, including the MMPs and TIMPs, which inhibit MMP activity [21][22][23][24]. Tissue remodeling is a continuous process, and a balance between matrix synthesis and breakdown is necessary to maintain the integrity of the genital tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Massip and colleagues generated a transgenic mouse model which induced Hoxa2 gene expression in a Cre-mediated way [3]. Crossing these mice with Col2a1-Cre transgenics [24] provoked an ectopic and persistent expression of Hoxa2 in every Col2a1 expressing cell, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction impacted the endochondral ossification process, resulting in a postnatal growth defect mimicking human PSS [3,4]. Indeed, whereas the transgenic mice were similar in size to the control animals at birth, they featured a significant but harmonious shortening of both the trunk and the appendicular skeleton as early as the day four.…”
Section: Introductionmentioning
confidence: 99%